The Multilingual CID-5: A New Tool to Study the Perception of Communicative Interactions in Different Languages - Manera, Valeria; Ianì, Francesco; Bourgeois, Jérémy; Haman, Maciej; Okruszek, Łukasz P.; Rivera, Susan M.; Robert, Philippe; Schilbach, Leonhard; Sievers, Emily; Verfaillie, Karl; Vogeley, Kai; von der Lühe, Tabea; et al. (Frontiers in Psychology, 2015)
The investigation of the ability to perceive, recognize and judge upon social intentions, such as communicative intentions, on the basis of body motion is a growing research area. Cross-cultural differences in ability to perceive and interpret biological motion, however, have been poorly investigated so far. Progress in this domain strongly depends on the availability of suitable stimulus material. In the present method paper, we describe the multilingual CID-5, an extension of the CID-5 database, allowing for the investigation of how non-conventional communicative gestures are classified and identified by speakers of different languages. The CID-5 database contains 14 communicative interactions and 7 non-communicative actions performed by couples of agents and presented as point-light displays. For each action, the database provides movie files with the point-light animation, text files with the 3-D spatial coordinates of the point-lights, and five different response alternatives. In the multilingual CID-5 the alternatives were translated into seven languages (Chinese, Dutch, English, French, German, Italian, and Polish). Preliminary data collected to assess the recognizability of the actions in the different languages suggest that, for most of the action stimuli, information presented in point-light displays is sufficient for the distinctive classification of the action as communicative vs. individual, as well as for identification of the specific communicative gesture performed by the actor in all the available languages.